Sex disparities in risk and risk factors for ischemic heart disease in the Asia-Pacific region. (29th August 2020) - Peters, Sanne AE; Woodward, Mark; Lam, Tai H; Fang, Xianghua; Suh, Il; Ueshema, Hirotsugu; Dobson, Annette J; Grobbee, Diederick E; Huxley, Rachel R; ,
Abstract: Background: Ischemic heart disease (IHD) is the leading cause of death and disability worldwide, with higher rates among men than women. Relatively few studies on risk factor associations are available from the Asia-Pacific region, especially with regard to sex differences. Our objective was to compare the relationships between modifiable risk factors and IHD in men and women from the Asia-Pacific region. Methods: Data from 600, 445 individuals from 44 studies from the Asia Pacific Cohort Studies Collaboration, an individual patient data overview, were used. Cox models were used to evaluate the effects of risk factors on fatal and non-fatal IHD separately in men and women from Australia and New Zealand (ANZ) and Asia. Results: Over a median follow-up of 6.7 years, 5695 IHD events were documented. The hazard ratio for IHD, comparing men with women, was 2.14 (95% CI 1.97–2.33) in ANZ and 1.88 (95% CI 1.54–2.29) in Asia. The age-adjusted prevalence of major risk factors was generally higher in men than women, especially in ANZ. Risk factors acted broadly similarly between men and women in both Asia and ANZ, with any indications of differences tending to favor men, rather than women. Conclusion: The excess risk of IHD observed in men compared with women in both Asia and ANZ may be, at least in part, a result of a more hazardous risk profile in men compared with women. The contribution of sex differences in the magnitude of the risk factor–disease associations is unlikely to be a contributing factor.